2023
DOI: 10.3390/jcm12030787
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cognitive Deficits in Borderline Personality Disorder with Early Traumas: A Mediation Analysis

Abstract: (1) Background: although studies of cognitive functions are still limited in borderline personality disorder (BPD), the initial evidence suggested that BPD patients have deficits of executive functions and social cognition. In addition, patients who report physical and psychic traumatic experiences in childhood and adolescence show considerable neurocognitive impairment and severe BPD symptoms. The present study has a twofold aim: (1) to evaluate the differences in neurocognitive performances between BPD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…To evaluate the EEG signal within each channel, statistical characteristics were utilized to assess central tendency, asymmetry, and peakedness. Spectral features were obtained by analyzing the frequency content of the EEG signals, with a specific focus on four frequency bands: delta (0.5-4 Hz), theta (4-8 Hz), alpha (8-13 Hz), and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Features reflecting the relative energy distribution across different frequency ranges were derived by computing power or spectral density within each frequency band.…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the EEG signal within each channel, statistical characteristics were utilized to assess central tendency, asymmetry, and peakedness. Spectral features were obtained by analyzing the frequency content of the EEG signals, with a specific focus on four frequency bands: delta (0.5-4 Hz), theta (4-8 Hz), alpha (8-13 Hz), and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Features reflecting the relative energy distribution across different frequency ranges were derived by computing power or spectral density within each frequency band.…”
Section: Feature Extractionmentioning
confidence: 99%
“…These impairments can disrupt patients’ daily lives, necessitating targeted interventions to address their specific cognitive challenges. Notably, cognitive impairment in these disorders’ manifests in various ways, including impulsivity, emotional dysregulation, impaired social cognition, problem-solving, decision-making impairments, processing speed reduction, and visuospatial processing deficits [ 18 , 19 ]. It has been reported that patients with BD II or BPD exhibit poor performance across multiple neurocognitive domains, similar in cognitive flexibility and set-shifting, decision-making, sustained and selective attention, and problem-solving [ 20 ].…”
Section: Introductionmentioning
confidence: 99%